DISAPPEARANCE OF ANTIBODIES IN COVID-19 MYTHS ORREALITY - Raza, Maqbool; Raza, Muhammed Ali; Cheema, De Emmal Asjad; Cheema, Maham Asjad; Rafique, Atif; Khan, Sarim Waleed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore the disappearance of neutralizing antibodies from patients, their myths, and facts. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital Multan Pakistan, from Jul 2021 to Aug 2021. Methodology: A total of 100 blood samples were collected from 100 COVID-19 patients. These 100 patients were followed up for a period of 3 months. Antibodies were determined with the modified neutralization assay method and enzyme-linked immuno-sorbent assay (ELISA). Results: The antibody level by NA and ELISA peaked on days 30-35 then decreased slightly. In multivariate analysis, patients aged 25-35, 36-56, and 57-84 years had a higher neutralizing antibody level than those aged 10-21 years. The patient with the worst clinical manifestation had a higher neutralizing antibody titer. In serum samples, IgG was undetectable at 18.3% and 11% and the geographical mean reciprocal titers dropped from 244 at 3-month period and neutralizing antibodies, the geographical mean reciprocal titers dropped from 874 at 3 months. Conclusion: All COVID-19 patients were seropositive and significantly neutralizing antibody response. Neutralizing antibody levels depend on the time after the onset of symptoms, age, and severity of the disease.